2021
DOI: 10.1187/cbe.20-12-0289
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Metacognition to Support Student Learning and Performance

Abstract: This essay highlights the key features of an evidence-based teaching guide on student metacognition that was created by an interdisciplinary team ( https://lse.ascb.org/evidence-based-teaching-guides/student-metacognition ). The guide focuses on ways instructors can support student learning strategies, encourage students to monitor and control their learning, and promote social metacognition during group work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 34 publications
0
93
0
4
Order By: Relevance
“…If summative assessments represent a large portion of the students’ final grades, it will be especially important to reach miscalibrated students early in the semester, ideally before the first summative assessment. These strategies add to the existing toolkit ( 8 ) that instructors can utilize to foster student metacognition and enhance learning in undergraduate science courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If summative assessments represent a large portion of the students’ final grades, it will be especially important to reach miscalibrated students early in the semester, ideally before the first summative assessment. These strategies add to the existing toolkit ( 8 ) that instructors can utilize to foster student metacognition and enhance learning in undergraduate science courses.…”
Section: Discussionmentioning
confidence: 99%
“…When students do not grasp the limits of their understanding, they are at risk of underperformance and academic failure ( 7 ). Instructor strategies to promote student metacognition have shown promise, but intervention studies have lagged behind foundational research in this area ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most interviewed students noted that receiving an unsatisfactory exam grade initially prompted the evaluation of their study strategies (Dye and Stanton, 2017). Researchers have suggested that instructors can integrate supports into biology courses to enhance students' metacognition (Stanton et al, 2021). For example, reflection assignments, answer keys that include the rationale for answers, and self-evaluations all seem to prompt Supporting Biology Success: Workshops metacognition (Stanton et al, 2015;Sabel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, reflection assignments, answer keys that include the rationale for answers, and self-evaluations all seem to prompt Supporting Biology Success: Workshops metacognition (Stanton et al, 2015;Sabel et al, 2017). Stanton et al (2021) provide further research-based suggestions in their review of metacognition for teachers. Based on prior work, these suggestions include teaching students to engage in metacognition as they prepare for, take, and evaluate their performance on exams, which are often new and challenging learning experiences for college biology students (Dye and Stanton, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Students will not know how to use their metacognitive skills if they are not taught as early as possible (Stanton et al, 2015). By empowering students' metacognition, teachers have helped them to learn and become better (Stanton et al, 2021).…”
Section: Introductionmentioning
confidence: 99%